Review of study on body positioning management of elderly patients with post-stroke hemiplegia (老年脑卒中偏瘫患者体位管理研究) - WANG Zhiqi (王志齐); HUANG Shan (黄山); DENG Ying (邓颖) (中西医结合护理)
Limb motor impairments are common after a stroke, seriously affecting the patients’ quality of life. The body positioning management, as an important rehabilitation technique, is effective to relieve the post-stroke movement disorders such as dystonia and spasticity. This paper reviewed studies on body positioning management and nursing of elderly patients with post-stroke hemiplegia, and provided reference for recovery of limb motor function, reducing risk of disability and improving the quality of life. (老年人脑卒中后多遗留不同程度的肢体活动障碍, 严重影响患者生活质量。体位管理可缓解老年脑卒中偏瘫患者肌张力和肢体痉挛, 预防畸形, 是重要的康复护理技术。本研究就老年脑卒中偏瘫患者体位管理要点及护理措施进行综述, 以期为促进老年偏瘫患者肢体功能康复, 减轻残疾, 提升生活质量提供参考依据。)